2018
DOI: 10.11648/j.aap.20180301.14
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Base Balance and Arterial Ion Concentrations in Rat Under Three Types of General Anaesthesia: Chronobiological Study

Abstract: The design and development of experimental, in vivo, chronobiological animal models may help reveal some of the relationships between circadian rhythms and biological functions. In vivo experiments require the use of appropriate anaesthesia, which should be selected according to their particular effect on the organism. The aim of study was to review the status of acid-base balance and ion concentration in arterial blood under common used general anaesthesias in experiments in dependence on the light-dark (LD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Hemodynamic parameters and blood gases were measured at baseline, during open chest and after closing of the chest. We found that hemodynamic features for MAP, HR and RPP were very similar between ventilation techniques and within physiological ranges 15 for both techniques of intubation (Figure 2 and Supplementary Table 1).…”
Section: Hemodynamic Parameters and Blood Gasesmentioning
confidence: 63%
See 3 more Smart Citations
“…Hemodynamic parameters and blood gases were measured at baseline, during open chest and after closing of the chest. We found that hemodynamic features for MAP, HR and RPP were very similar between ventilation techniques and within physiological ranges 15 for both techniques of intubation (Figure 2 and Supplementary Table 1).…”
Section: Hemodynamic Parameters and Blood Gasesmentioning
confidence: 63%
“…19 We have shown that using nose cone ventilation during anesthesia, it is possible to maintain: adequate blood circulation presented by heart rate, mean arterial pressure and rate pressure product; normal acid-base status as indicated by that pH, pCO 2 , HCO 3 and lactate that were within normal respective reference intervals; and normal oxygen uptake in the lungs assessed by pO 2 blood oxygenation. [15][16][17][18] The learning curve for this technique is shallow and no special instruments except the nose cone are necessary. Even with experience in endotracheal intubation technique, the nose cone ventilation is considerably easier to perform.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations